Analysis Of Solar Power Plant Utilization For Public Street Lighting In Probolinggo, Jawa Timur, Indonesia - Saputri, Fahmy Rinanda; Richard Stanlee, Adrix; Hadi Prasetya, Indra; Delana Wijaya, Sarah (International Journal of Science, Technology & Management, 2023)
Fossil fuels namely coal, petroleum, and natural gas have long been chosen as the main energy sources in meeting global energy needs. However, fossil fuels have the main problem in that their amount is limited and causes global warming. To overcome these problems, renewable energy such as solar energy can be used. Solar energy can be converted into electrical energy by using solar panels. The installation of a solar power plant certainly requires a large budget, to check its feasibility and can be simulated using PVSyst and RETScreen. In particular, PVSyst is used to search for the amount of material needed, the power capacity produced, and energy losses (there is energy lost). Then, RETScreen is used to calculate photovoltaic installation costs, operational and maintenance costs after photovoltaic installation, and emissions. Probolinggo has enormous potential to use solar power plants with Photovoltaic modules. This study simulates the installation of photovoltaic modules in Probolinggo which still has shortcomings in terms of public street lighting. From the simulations carried out, it can be concluded that Probolinggo is feasible for the installation of the solar power plant. With PVSyst, the total number of photovoltaic modules installed is 15,112 pieces. The total power generated is 10,145 MWh. Then, by using RETScreen, a photovoltaic installation fee of Rp142,978,410,000 was obtained. and annual maintenance costs of Rp1,281,870,000.